A Nucleoporin NUP58 modulates responses to drought and salt stress in maize (Zea mays L.). (July 2022) - Liu, Zhixue; Abou-Elwafa, Salah Fatouh; Xie, Jiarong; Liu, Yajing; Li, Siyuan; Aljabri, Maha; Zhang, Dongling; Gao, Fengran; Zhang, Lili; Wang, Zhiyong; Sun, Chongyu; Zhu, Bingqi; et al.
Abstract: Nuclear pore complex (NUP) is the main transport channel between cytoplasm and nucleoplasm, which plays an important role in stress response. The function of NUPs was widely reported in yeast and vertebrate but rarely in plants. Here, we identified a nuclear pore complex ( ZmNUP58 ), that is tightly associated with drought and salt tolerance phenotype accompanied with phenotypic and physiological changes under drought and salt stress. The overexpression of ZmNUP58 in maize ( Zea mays L.) significantly promotes both chlorophyll content and activities of antioxidant enzymes under drought- and salt-stressed conditions. RNA-Seq analysis showed that ZmNUP58 could regulate the expression of genes related to phytohormone synthesis and signaling, osmotic adjustment substances, antioxidant enzyme system, cell wall biosynthesis, glucose metabolism and aquaporin. The results provide novel insights into the regulatory role of ZmNUP58 in improving drought and salt tolerance through regulating phytohormone and other stress response genes in maize. Highlights: Nuclear pore complex (NUP) is the main transport channel between cytoplasm and nucleoplasm, which plays an important role in stress response. The overexpression of ZmNUP58 can significantly strengthen the tolerance to drought stress and salt stress. The overexpression of ZmNUP58 in maize significantly promotes both chlorophyll content and activities antioxidant enzymes under drought and salt conditions. ZmNUP58 could regulate the expression of genes related to phytohormone synthesis and signaling, osmotic adjustment substances, antioxidant enzyme system, cell wall biosynthesis, glucose metabolism and aquaporin.